Teaching robotic surgery skills: comparing the methods of generalists and subspecialists. Issue 4 (30th July 2013) - Pickett, Stephanie D.; James, Rebecca L.; Mahajan, Sangeeta T.
Abstract Background To compare opinions of general and subspecialty obstetricians and gynecologists regarding teaching robotic surgery (RS) to residents. Methods After obtaining IRB approval, 2189 gynecologic surgeons trained on the DaVinci Surgical System® (Intuitive Surgical, Sunnydale, CA) were asked to complete an online survey. Anonymous responses were obtained and compared using the chi‐squared test, including opinions on training residents in RS. Results Of these 303 respondents, 161 practiced general obstetrics and gynecology ('generalists'), and 138 were self‐described 'subspecialists' (+/‐ fellowship training). The majority of subspecialists (82%) taught residents, and 63% allowed resident participation. Only 44% of generalists taught residents, and 36% allowed participation. Regarding ideal RS training time, generalists favored residency (39%), while subspecialists favored fellowship. (46%, P < 0.001) Conclusions While many generalists and subspecialists incorporate training residents into their robotic cases, there is still disparity regarding the extent of participation. Standardized training curriculums should be a goal of residencies with RS. Copyright © 2013 John Wiley & Sons, Ltd.